Perkembangan Dan Peninggalan Dinasti Moghul Di India 1525-1857 - Muhammad Basri; Nur Saadah; Ijar Salna (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
There are three aims of writing this article: first to understand the identity of the Moghul kingdom;the second is to understand the growth of the Moghul empire, and the third is to study some of themisfortunes of the Moghul empire, such as in the fields of politics, socialism, and politics, art, andso on. The founder of the Moghul empire was Kutbu'ddin Aibak (1206–11), who was able toestablish an independent Islamic kingdom in India. There were three rulers: Aurangzib, ShahJahan, and Sultan Akbar. Sultan Akbar also combined Islamic and Hindu civilization and had aruler who was able to maintain the stability of the sultanate. On the other hand, Shah Jahan gaveaway a few secrets, such as the famous Taj Mahal. Other Aurangzib people are still struggling toimprove their education. However, after Aurangzib succeededin establishing the unity of thekingdom, the Moghuls were reluctant to become the few remaining kingdoms. The imprisonment ofthe Sepoys in 1857 marked the end of the Moghul era. The English were different from the Moghulmonarchy.